Spatiotemporal Brain Dynamics of Empathy for Pain and Happiness in Friendship - Wang, Yiwen; Song, Juan; Guo, Fengbo; Zhang, Zhen; Yuan, Sheng; Cacioppo, Stephanie (Frontiers in Behavioral Neuroscience, 2016)
Although a large number of fMRI studies have investigated the neural basis of empathy, little is known about its spatiotemporal dynamics. Moreover, most of the previous studies on empathy have focused on empathy for pain rather than empathy for positive emotions, such as happiness. In the present study, we addressed this question by investigating the spatiotemporal dynamics of different kinds of empathy by combining electrophysiological recordings with a behavioral priming empathy task involving negative and positive emotions. Electrical brain activity and behavioral data were analyzed from 30 subjects (12 males and 18 females). Half of the subjects performed a behavioral task on empathy for pain (EP task), while the other half performed a behavioral task on empathy for happiness (EH task). In each task, participants viewed prime photographs of either: 1) a stranger; or 2) a close friend (primes) followed by target photographs showing either a hand being hurt (or not; targets in the EP task), or a hand in happy circumstances (or not; targets in the EH task). In each task, participants were asked to judge the target situation and report whether they could feel the pain (in EP task) or the happiness (in the EH task), as a function of the primes i.e., either from the close friend’s or from the stranger’s perspective. Overall, our results suggest that taking the perspective of a close friend (compared to that of a stranger), as a prime stimulus, does have a dual-stage effect on empathy that is characterized by an early modulation for pain and later modulations for both pain and happiness. The early differences between friend and stranger primes for pain (but not for happiness) suggest that empathy for pain is an automatic process that has been socially learned and passed among friends. On the other hand, the later differences observed between stranger and friend primes suggest additional cognitive appraisal take place for both pain and happiness. Our results suggest that it takes more cognitive attentional efforts to judge a stranger’s happiness than a friend’s, whereas the opposite is true for pain.